First Reported Case of Endoscopic Ultrasound-Guided Core Biopsy Yielding Diagnosis of Primary Adrenal Leiomyosarcoma - Shaunak R. Mulani; Patrick Stoner; Alexander Schlachterman; Hans K. Ghayee; Li Lu; Anand Gupte (Case Reports in Gastrointestinal Medicine)
Primary adrenal leiomyosarcoma (PAL) is an extremely rare mesenchymal tumor with only a few isolated case reports in the medical literature. Endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) or endoscopic ultrasound-guided core biopsy (EUS-CB) is a safe, effective modality for sampling lesions in the gastrointestinal tract and adjacent organs, including the adrenal glands. We describe the case of a 50-year-old male presenting with abdominal pain and unintentional weight loss over the course of one year. CT imaging revealed an 8.1 cm heterogeneous left adrenal mass with PET-confirmed metastases to the liver and lung. Pheochromocytoma was ruled out. Adrenal cortical carcinoma was the other critical differential diagnosis. As the patient was not a candidate for surgery, an EUS-FNA and CB were performed on this left adrenal mass revealing a spindle cell neoplasm with extensive necrosis confirming the diagnosis of primary leiomyosarcoma. The patient was treated with chemotherapy with palliative radiation. This case demonstrates the utility of EUS-FNA or CB as modalities that can aid in the diagnosis of adrenal lesions in specific circumstances.